2014
DOI: 10.1016/j.ijggc.2014.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Possible ways to minimize nitrosation reactions during post-combustion CO2 capture process

Abstract: The formation and any emission of nitrosamines in a post-combustion CO capture process are of great interest over the past few years even though its concentration is quite low. In the present research, bench scale nitrosation experiments were conducted using morpholine, a representative of secondary amines, with NO 2 gas and flue gas. Laboratory experiments with 5 M morpholine with 100 ppm NO 2 gas resulted in 88 µg/g nitrosomorpholine (NSMO) in 6 h and 450 µg/g in 24 h. However, coal derived flue gas gave onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…However, in addition to having active primary and secondary amine groups, the PEI‐10k also contains the less‐active tertiary amine with the ratio of the primary/secondary/tertiary amines of 1:2:1, respectively. Tertiary amines are active for CO 2 adsorption under hydrous conditions only . Since the PEI‐423/MPS and PEI‐10k/MPS samples contain similar nitrogen contents, it is not surprising that, at the same temperature, the activity of PEI‐423/MPS towards CO 2 adsorption was about 1.25 times higher than the activity of PEI‐10k/MPS (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…However, in addition to having active primary and secondary amine groups, the PEI‐10k also contains the less‐active tertiary amine with the ratio of the primary/secondary/tertiary amines of 1:2:1, respectively. Tertiary amines are active for CO 2 adsorption under hydrous conditions only . Since the PEI‐423/MPS and PEI‐10k/MPS samples contain similar nitrogen contents, it is not surprising that, at the same temperature, the activity of PEI‐423/MPS towards CO 2 adsorption was about 1.25 times higher than the activity of PEI‐10k/MPS (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Nitrite scavenging has been examined to reduce nitrosamine formation in amine solvents. Previous work from our group showed that nitrite scavengers are effective at inhibiting the formation of nitrosomorpholine from morpholine by removing the key nitrite reactant after it is formed from NO x dissolving in the amine solvent . Several other additives, including ascorbic acid and cysteine, can be reasonably effective at reducing the formation of nitrosopiperazine (NPZ) in a PZ–AMP solvent …”
Section: Introductionmentioning
confidence: 99%
“…Nielsen et al also showed the thermal degradation of NPZ and formation of NPZ in the absorber yielded a steady-state concentration of near 1 mmol/kg . In contrast to these reports, nitrosamine formation from morpholine is enhanced at higher temperatures up to 145 °C . Therefore, the thermal degradation temperature may vary for a different of nitrosamines, and more research is likely necessary to tailor this approach for different solvents and solvent blends in which different nitrosamines are expected to form.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These nitrosamines are of major concern due to their environmental and health impacts. Some inhibitors have been recently reported by our group to prevent nitrosation reaction under post combustion CO 2 capture conditions [6].…”
Section: Introductionmentioning
confidence: 99%